Low‐Crystalline AuCuIn Catalyst for Gaseous CO2 Electrolyzer. Issue 8 (22nd January 2022) - Han, Gyeong Ho; Kim, Junhyeong; Jang, Seohyeon; Kim, Hyunki; Guo, Wenwu; Hong, Seokjin; Shin, Junhyeop; Nam, Inho; Jang, Ho Won; Kim, Soo Young; Ahn, Sang Hyun
Abstract: Despite its importance for the establishment of a carbon‐neutral society, the electrochemical reduction of CO2  to value‐added products has not been commercialized yet because of its sluggish kinetics and low selectivity. The present work reports the fabrication of a low‐crystalline trimetallic (AuCuIn) CO2  electroreduction catalyst and demonstrates its high performance in a gaseous CO2  electrolyzer. The high Faradaic efficiency (FE) of CO formation observed at a low overpotential in a half‐cell test is ascribed to the controlled crystallinity and composition of this catalyst as well as to its faster charge transfer, downshifted d‐band center, and low oxophilicity. The gaseous CO2  electrolyzer with the optimal catalyst as the cathode exhibits superior cell performance with a high CO FE and production rate,  outperforming state‐of‐the‐art analogs. Thus, the obtained results pave the way to the commercialization of CO2  electrolyzers and promote the establishment of a greener society. Abstract : Low‐crystalline AuCuIn is proposed as effective catalyst for cathode in gaseous CO2  electrolyzer to produce CO selectively, owing to its suitable binding energy, fast electron transfer, enhanced mass transfer, and suppressed H2  evolution. The electrolyzer demonstrates that a CO partial current density reaches 220.1 mA cm −2  with a Faradaic efficiency of ≈100% at a low cell voltage of 2.8 Vcell .